CRISPR-Cas9 in basic and translational aspects of cancer therapy - Maryam Samareh Salavatipour; Zahra Poursalehi; Negin Hosseini Rouzbahani; Sohaib Mohammadyar; Mohammad Vasei (BioImpacts)
Introduction: The discovery of gene editing techniques has opened a new era within the field of biology and enabled scientists to manipulate nucleic acid molecules. CRISPR-Cas9 genome engineering has revolutionized this achievement by successful targeting the DNA molecule and editing its sequence. Since genomic changes are the basis of the birth and growth of many tumors, CRISPR-Cas9 method has been successfully applied to identify and manipulate the genes which are involved in initiating and driving some neoplastic processes. Methods: By review of the existing literature on application of CRISPR-Cas9 in cancer, different databases, such as PubMed and Google Scholar, we started data collection for "CRISPR-Cas9", "Genome Editing", "Cancer", "Solid tumors", "Hematologic malignancy" "Immunotherapy", "Diagnosis", "Drug resistance" phrases. Clinicaltrials.gov, a resource that provides access to information on clinical trials, was also searched in this review. Results: We have defined the basics of this technology and then mentioned some clinical and preclinical studies using this technology in the treatment of a variety of solid tumors as well as hematologic neoplasms. Finally, we described the progress made by this technology in boosting immune-mediated cell therapy in oncology, such as CAR-T cells, CAR-NK cells, and CAR-M cells. Conclusion: CRISPR-Cas9 system revolutionized the therapeutic strategies in some solid malignant tumors and leukemia through targeting the key genes involved in the pathogenesis of these cancers.